Glaciological Studies of the Institute of Geography, RAS, on the Elbrus Mount in 2023 - I. I. Lavrentiev; A. M. Smirnov; P. A. Toropov; N. E. Elagina; T. D. Kiseleva; E. D. Drozdov; A. I. Degtyarev (Лëд и снег)
In June 2023, mass-balance and meteorological observations on Elbrus were expanded: monitoring of the Mikelchiran glacier on the northern slope of the volcano was added to the permanent observations on the southern slope (Garabashi glacier). Such synchronized observations on the opposite macro-slopes of Elbrus have not been carried out before.